2019
DOI: 10.3390/s19132894
|View full text |Cite
|
Sign up to set email alerts
|

Recording of Bipolar Multichannel ECGs by a Smartwatch: Modern ECG Diagnostic 100 Years after Einthoven

Abstract: Aims: Feasibility study of accurate three lead ECG recording (Einthoven I, II and III) using an Apple Watch Series 4. Methods: In 50 healthy subjects (18 male; age: 40 ± 12 years) without known cardiac disorders, a 12-lead ECG and three bipolar ECGs, corresponding to Einthoven leads I, II and III were recorded using an Apple Watch Series 4. Einthoven I was recorded with the watch on the left wrist and the right index finger on the crown, Einthoven II with the watch on the left lower abdomen and the right index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 11 publications
3
57
0
1
Order By: Relevance
“…As an interesting finding, the mean age of our included patients was 63.6 ± 14.0 years, which reflects an older age in comparison to other studies [ 14 , 15 ]. This is important because one might think that it would be very difficult for the elderly to record ECG with a smartwatch, but our experience showed that the elderly without motor or mental problems could undertake this task confidently after a very short training.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…As an interesting finding, the mean age of our included patients was 63.6 ± 14.0 years, which reflects an older age in comparison to other studies [ 14 , 15 ]. This is important because one might think that it would be very difficult for the elderly to record ECG with a smartwatch, but our experience showed that the elderly without motor or mental problems could undertake this task confidently after a very short training.…”
Section: Discussionmentioning
confidence: 48%
“…Although we are not the first group who reported the utility and description of this technique, our study has confirmed its validity in a relatively large sample. Our previous understanding regarding the smartwatch ECGs were limited to the findings of several case reports and case series [ 7 , 27 , 28 , 29 , 30 ], and three studies on around 50–100 patients [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations